Revision of Pazala Moore, 1888: The Graphium (Pazala) mandarinus (Oberthür, 1879) Group, with Treatments of Known Taxa and Descriptions of New Species and New Subspecies (Lepidoptera: Papilionidae) - Hu, Shao-Ji; Cotton, Adam M.; Condamine, Fabien L.; Duan, Kuang; Wang, Rong-Jiang; Hsu, Yu-Feng; Zhang, Xin; Cao, Jun (Zootaxa, 2018)
The previously recognised closely related species Graphium (Pazala) mandarinus (Oberthür, 1879) and G. (P.) sichuanica (Koiwaya, 1993) are shown to comprise seven species as a result of both molecular and morphological analysis. Molecular dating analysis is also performed on the mandarinus group in order to investigate the divergence time of the taxa. Two taxa, G. (P.) garhwalica (Katayama, 1988) stat. nov. and G. (P.) paphus (de Nicéville, 1886) stat. nov., are raised from subspecific to specific status; G. (P.) hoeneanus Cotton & Hu nom. nov., stat. rev. is separated from sichuanica at species level; and two previously unrecognised new species, G. (P.) daiyuanae Hu, Zhang & Cotton sp. nov. and G. (P.) confucius Hu, Duan & Cotton sp. nov. are described from Vietnam and China respectively, the latter being sympatric with nominate G. (P.) mandarinus. The identity of the lectotype of G. (P.) mandarinus is confirmed and a lectotype is designated for the taxon Papilio Glycerion Gray, 1831. A new subspecies of G. (P.) mandarinus is described from western Yunnan and northern Myanmar, G. (P.) mandarinus stilwelli Cotton & Hu ssp. nov.